The Behavioral Ecology of the Tibetan Macaque - Li, Jin-Hua.; Sun, Lixing; Kappeler, Peter M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book summarizes the multi-disciplinary results of one of China s main primatological research projects on the endemic Tibetan macaque (Macaca thibetana), which had continued for over 30 years, but which had never been reported on systematically. Dedicated to this exceptional Old World monkey, this book makes the work of Chinese primatologists on the social behavior, cooperation, culture, cognition, group dynamics, and emerging technologies in primate research accessible to the international scientific community. One of the most impressive Asian monkeys, and the largest member of its genus, the Tibetan macaque deserves to be better known. This volume goes a long way towards bringing this species into the spotlight with many excellent behavioral analyses from the field.- Frans de Waal, Professor of Psychology, Emory University, USA. Macaques matter. To understand primate patterns and trends, and to gain important insight into humanity, we need to augment and expand our engagement with the most successful and widespread primate genus aside from Homo. This volume focuses on the Tibetan macaque, a fascinating species with much to tell us about social behavior, physiology, complexity and the macaque knack for interfacing with humans. This book is doubly important for primatology in that beyond containing core information on this macaque species, it also reflects an effective integrated collaboration between Chinese scholars and a range of international colleagues exactly the type of collaborative engagement primatology needs. This volume is a critical contribution to a global primatology. - Agustín Fuentes, Professor of Anthropology, University of Notre Dame, USA. I have many fond memories of my association with Mt. Huangshan research beginning in 1983, when together with Professor Qishan Wang we established this site. It is such a beautiful place and I miss it. It is gratifying to see how far research has progressed since we began work there, becoming more internationalized and very much a collaborative endeavor under the long-term direction of Professor Jin-Hua Li and colleagues. This book highlights the increased interest in this species, representing a variety of disciplines ranging from macro aspects of behavior, cognition and sociality, to micro aspects of microbes, parasites and disease, authored by a group of renowned Chinese and international primatologists. I applaud their efforts and expect more interesting work to come from this site in the years ahead.- Kazuo Wada, Professor Emeritus, Kyoto University, Japan.
Part I: Introduction -- Chapter 1: Recent developments in primatology and their relevance to the study of Tibetan macaques -- Part II: Social Behavior and Dynamics in Tibetan Macaques -- Chapter 2: Social and Life History Strategies of Tibetan Macaques at Mt. Huangshan -- Chapter 3: Size Matters in Primate Societies: How Social Mobility Relates to Social Stability in Tibetan and Japanese Macaques -- Chapter 4: Behavioral exchange and interchange as strategies to facilitate social relationships in Tibetan macaques -- Chapter 5: Social relationships impact collective decision-making in Tibetan macaques -- Chapter 6: Considering Social Play in Primates: A Case Study in Juvenile Tibetan Macaques (Macacathibetana) -- Chapter 7: The Vocal Repertoire of Tibetan Macaques (Macacathibetana) and Congeneric Comparisons -- Chapter 8: Tibetan Macaque Social Style: Co-variant and Quasi-independent Evolution -- Part III: Evolution of Rituals: Insights from Bridging Behavior -- Chapter 9: Preliminaryobservations of female-female bridging behavior in Tibetan macaques (Macacathibetana) at Mt. Huangshan, China -- Chapter 10: Bridging Behavior and Male-Infant Interactions in Macacathibetana and M. assamensis: Insight into the Evolution of Social Behavior in the sinica Species-group of Macaques -- Part IV: Livingwith Microbes, Parasites, and Diseases -- Chapter 11: The gut microbiome of Tibetan macaques: composition, influencing factors and function in feeding ecology -- Chapter 12: Medicinal Properties in the Diet of Tibetan Macaques at Mt. Huangshan - A Case for Self-medication -- Chapter 13: Primate infectious disease ecology: Insights and future directions at the human-macaque interface -- Part V: Emerging Technologies in Primatology -- Chapter 14: High field MRI technology for behavioral and cognitive studies in macaques in vivo.
Keywords: Psychobiology; Human behavior; Physical anthropology; Cognitive psychology; Animal welfare -- Moral and ethical aspects; Animal migration; Animal culture; Behavioral Neuroscience; Physical-Biological Anthropology; Cognitive Psychology; Animal Ethics; Animal Migration; Animal Science